If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 1) * sqare = 3x + -1 Reorder the terms: 4(1 + x) * sqare = 3x + -1 Reorder the terms for easier multiplication: 4aeqrs(1 + x) = 3x + -1 (1 * 4aeqrs + x * 4aeqrs) = 3x + -1 (4aeqrs + 4aeqrsx) = 3x + -1 Reorder the terms: 4aeqrs + 4aeqrsx = -1 + 3x Solving 4aeqrs + 4aeqrsx = -1 + 3x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Reorder the terms: 1 + 4aeqrs + 4aeqrsx + -3x = -1 + 3x + 1 + -3x Reorder the terms: 1 + 4aeqrs + 4aeqrsx + -3x = -1 + 1 + 3x + -3x Combine like terms: -1 + 1 = 0 1 + 4aeqrs + 4aeqrsx + -3x = 0 + 3x + -3x 1 + 4aeqrs + 4aeqrsx + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 1 + 4aeqrs + 4aeqrsx + -3x = 0 The solution to this equation could not be determined.
| 9x+10=45+x | | 5x+22=13x-72 | | (10y^5)-(15y^4)-(25y^3)=0 | | 5xy(2xy-3)= | | (6X-1)(-5-4X)= | | 4x(5x+2x-7)= | | 59-4x=23x+17 | | (4x+5)(-7X+4)= | | 2x^2+x+5=1 | | 8x-41=6x-9 | | 4x-15=7(2x-3) | | (x+1/2)(2x-1/3) | | 3(x-2)=5x+12 | | 2cx+4dx= | | 3/1-1/3 | | 3-1/3 | | x^3-4=3 | | 4x^2-21x+42=6x+7 | | x^2+12x+21=3x+3 | | X*(4/100)+X=205 | | 2y^2+y=-11y | | x^2-11x-1=0 | | 5x+26=14x-83 | | X+(4*X)/100=0 | | y-6=-y^2 | | 3x^2-21x-6=0 | | y=-8-3x/2 | | X+(4*X)/100 | | X+(X*4/100)=205 | | [x+4]+8=2 | | abs(x-4)=5 | | Ix-4l=5 |